OP0082 TEMPORAL TRENDS OF BISPHOSPHONATE DISCONTINUATION AND FACTORS ASSOCIATED WITH ALENDRONATE DISCONTINUATION AND RESTART AT POPULATION LEVEL. (June 2019) - Adami, Giovanni; Jaleel, Ayesha; Curtis, Jeffrey; Chen, Rui; Yun, Huifeng; Daigle, Shanette; Arora, Tarun; Danila, Maria; Wright, Nicole; Cadarette, Suzanne; Mudano, Amy; Foster, Jeff; et al.
Abstract : Background: Bisphosphonates are the most commonly used class of osteoporosis medication worldwide. Rare adverse events related to long-term use of bisphosphonates have raised interest in planned temporary drug discontinuation. Due to chronicity of osteoporosis, restarting osteoporosis medication is likely to be needed after such a discontinuation. Trends in the discontinuation and the restart of bisphosphonates and their reasons are not fully understood. Objectives: We investigated the temporal trends of bisphosphonate discontinuation from 2010 to 2015 and evaluated the factors associated with alendronate only discontinuation and restart of any osteoporosis medication at a population level. Methods: To determine the temporal trends of discontinuation (at least 12 months without prescription claims) from 2010 to 2015, we identified a cohort of women with long-term bisphosphonate therapy (medication possession ratio (MPR) ≥ 80% for at least 3 continuous years) derived from the enhanced 5% Medicare sample and a cohort of beneficiaries with evidence of osteoporosis (defined using diagnosis and fracture codes, and medication claims). We used a case-crossover design, nested within the cohort study, to identify factors associated with discontinuation of long-term alendronate therapy and restart of any osteoporosis medication. We used conditional logistic regression adjusted for potential confounders to compare factors associated with alendronate discontinuation and osteoporosis therapy restart in the hazard period (120 days) referent to the preceding control periods (120 days). Results: We identified a total of 73, 800 women with exclusive long-term alendronate (59, 251), risedronate (6, 806), or zoledronic acid (7, 743) use, respectively, of which 26, 281 (35.6%) women discontinued therapy. The proportion of long-term bisphosphonate users who discontinued therapy increased from 1.7% in 2010 to 14.0% in 2012, and remained relatively stable thereafter (Figure 1 ) After adjustment, factors most strongly associated with the discontinuation of alendronate included: a new prescription of benzodiazepines (adjusted Odds Ratio [aOR] = 2.5, 95% CI [2.1, 3.0]), prior dual-energy X-ray absorptiometry (DXA) scan (aOR = 1.8, 95% CI [1.7, 2.0]), skilled nursing facility care utilization (aOR = 1.8, 95% CI [1.6, 2.1]). Factors most strongly associated with the restart of any osteoporosis medication were: performing DXA scan (aOR = 9.9, 95% CI [7.7, 12.6]), fragility fracture (aOR = 2.8, 95% CI [1.8, 4.5]), and osteoporosis or osteopenia diagnosis (aOR = 2.5, 95% CI [2.0, 3.1]). Conclusion: We describe temporal trends in bisphosphonate discontinuations and factors associated with discontinuation of alendronate and restart of osteoporosis therapy. From 2010 to 2015, approximately one-third of women with long-term bisphosphonate treatment discontinued treatment for ≥12 months. We observed an increasing trend in discontinuation from 2010 to 2012, which remained steady through 2015. Factors associated with discontinuation of alendronate were associated with worsening of overall health status, while factors traditionally associated with worsening bone health were associated with restart of osteoporosis medication. Disclosure of Interests: Giovanni Adami: None declared, Ayesha Jaleel: None declared, Jeffrey Curtis: None declared, Rui Chen: None declared, Huifeng Yun Grant/research support from: BMS, Pfizer, Shanette Daigle: None declared, Tarun Arora Grant/research support from: Amgen, Maria Danila Grant/research support from: Pfizer, Inc., Consultant for: Sanofi Genzyme & Regeneron, Nicole Wright Grant/research support from: Amgen, Consultant for: NortonRose Fulbright/Pfizer, Suzanne Cadarette: None declared, Amy Mudano: None declared, Jeff Foster: None declared, Kenneth Saag Grant/research support from: Amgen, Ironwood/AstraZeneca, Horizon, SOBI, Takeda, Consultant for: Abbvie, Amgen, Ironwood/AstraZeneca, Bayer, Gilead, Horizon, Kowa, Radius, Roche/Genentech, SOBI, Takeda, Teijin